Inya: Wet Nurse and Succesful Regeneration of the Mataram Islamic Court Authorities in the Past - Sumarno, Sumarno; Fibiona, Indra; Lestari, Siska Nurazizah (Indonesian Historical Studies, 2024)
The fame of Islamic Mataram, a kingdom that encompassed Java and its surroundings, is reflected in its strong Javanese culture. Since the Mataram era, Javanese culture has been an important part of Javanese life. One of the main characteristics of the culture that is inherent in the lives of Javanese people is Inya. Inya is the term for the nurse or mother of the king's baby who is considered a symbol of the fame of the Islamic Mataram kingdom. This study discusses the ins and outs of Inya and its contribution to the regeneration of the rulers of the Islamic Mataram palace. The method used in this study is the Historical method. Data search focused on literature studies related to the empowerment of Inya in the past. The results of this study indicate that Inya has a very important role in the regeneration of the rulers of the Islamic Mataram palace. Inya has the task of raising and caring for the king's baby. Inya also has an obligation to educate and train the king's baby according to the procedures and customs of the Islamic Mataram community.